2021
DOI: 10.21608/ejhc.2021.197202
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Job Crafting, Nurses' Job Satisfaction and Counterproductive Work Behaviors

Abstract: Background: Job crafting can be considered as proactive behaviour from nurses to initiate changes in their job demands and resources to make their jobs more meaningful, satisfying and engaging in more productive behaviour. Aim of the study: Identify relation between job crafting, nurses' job satisfaction and counterproductive work behaviors Research design: A descriptive correlational study design was utilized in the present research. Sample: All the available nurses (390) were recruited in the current study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The final set of hypotheses examined the effect of job crafting on JS, and the results were in line with existing studies (Abou Shaheen & Aly Mahmoud, 2021;de Beer et al, 2016;Ogbuanya & Chukwuedo, 2017). It was observed that SSJR had a positive relationship with JS, and it can be due to supervisor and peer support (de Beer et al, 2016;Tims et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…The final set of hypotheses examined the effect of job crafting on JS, and the results were in line with existing studies (Abou Shaheen & Aly Mahmoud, 2021;de Beer et al, 2016;Ogbuanya & Chukwuedo, 2017). It was observed that SSJR had a positive relationship with JS, and it can be due to supervisor and peer support (de Beer et al, 2016;Tims et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…The result of this study is not comparable to the findings of Abou Shaheen and Aly Mahmoud, which demonstrated the majority of nurses had a low level of job crafting due to a lack of understanding of the job. It also found the majority of nurses had a low level of satisfaction [ 33 ]. These results may be due to the nurses working in university hospitals being under a harsh atmosphere and usually being overburdened with an increased number of patients and, simultaneously, without a financial reward appropriate to their effort.…”
Section: Discussionmentioning
confidence: 99%